IDENTITAS SOSIAL ANGGOTA KOMUNITAS MAHASISWA MUSLIM PATANI THAILAND - Aqim Laila; Dienita Dwi Rahmawati; Muhammad Alaudin Candra Pratama; Suraida Haya; Siti Hikmah Anas (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Muslim Patani students studying in Indonesia face challenges as foreign students and a minority group, especially in forming their identity in a new environment. This study aims to understand how social identity is formed, maintained, and interpreted by members of the Muslim Patani student community through their experiences in the community. This study uses a qualitative approach with a phenomenological method to explore the subjective experiences of community members. Subjects were selected using purposive sampling, and data were collected through in-depth interviews. Data analysis was conducted using thematic analysis techniques to identify patterns of meaning that emerged from the participants' experiences. The results show that the Patani Muslim student community plays an important role as a safe social space and that social identity is formed through active involvement in the community, such as participation in decision-making, joint activities, and opportunities to express one's potential. In addition, social identity is maintained through consistent social, cultural, and religious practices, as well as discussions about the conditions of the Patani community in their home country. ABSTRAK Mahasiswa Muslim Patani yang menempuh pendidikan di Indonesia menghadapi tantangn sebagai mahasiswa rantau dan kelompok minoritas terutama dalam pembentukan identitas diri di lingkungan baru. Penelitian ini bertujuan untuk memahami bagaimana identitas sosial terbentuk, dipertahankan, dan dimaknai oleh anggota komunitas mahasiswa Muslim Patani melalui pengalaman mereka dalam komunitas. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologis untuk menggali pengalaman subjektif para anggota komunitas. Pemilihan subjek menggunakan purposive sampling dan data dikumpulkan melalui wawancara mendalam. Analisis data dilakukan dengan teknik analisis tematik untuk mengidentifikasi pola makna yang muncul dari pengalaman partisipan. Hasil penelitian menunjukkan bahwa komunitas mahasiswa Muslim Patani berperan penting sebagai ruang sosial yang aman dan identitas sosial terbentuk melalui keterlibatan aktif dalam komunitas, seperti partisipasi dalam pengambilan keputusan, kegiatan bersama, serta kesempatan mengekspresikan potensi diri. Selain itu, identitas sosial dipertahankan melalui praktik sosial, budaya, dan keagamaan yang dijalankan secara konsisten, serta diskusi mengenai kondisi masyarakat Patani di negara asal.